Synthesis and Characterization of a Silica-Based Drug Delivery System for Spinal Cord Injury Therapy - Sun, Guodong; Zeng, Shenghui; Liu, Xu; Shi, Haishan; Zhang, Renwen; Wang, Baocheng; Zhou, Changren; Yu, Tao (Nano-Micro Letters, 2019)
Acute inflammation is a central component in the progression of spinal cord injury (SCI). Anti-inflammatory drugs used in the clinic are often administered systemically at high doses, which can paradoxically increase inflammation and result in drug toxicity. A cluster-like mesoporous silica/arctigenin/CAQK composite (MSN-FC@ARC-G) drug delivery system was designed to avoid systemic side effects of high-dose therapy by enabling site-specific drug delivery to the spinal cord. In this nanosystem, mesoporous silica was modified with the FITC fluorescent molecule and CAQK peptides that target brain injury and SCI sites. The size of the nanocarrier was kept at approximately 100 nm to enable penetration of the blood–brain barrier. Arctigenin, a Chinese herbal medicine, was loaded into the nanosystem to reduce inflammation. The in vivo results showed that MSN-FC@ARC-G could attenuate inflammation at the injury site. Behavior and morphology experiments suggested that MSN-FC@ARC-G could diminish local microenvironment damage, especially reducing the expression of interleukin-17 (IL-17) and IL-17-related inflammatory factors, inhibiting the activation of astrocytes, thus protecting neurons and accelerating the recovery of SCI. Our study demonstrated that this novel, silica-based drug delivery system has promising potential for clinical application in SCI therapy. Highlights: 1 With good biocompatibility, a silica-based drug delivery system was prepared and used effectively in vivo to prolong the duration of drug treatment. 2 The prepared system can target spinal cord injury directly. Additionally, due to its small size (approximately 100 nm), it can penetrate the blood-spinal cord barrier. 3 This system reduced the expression of interleukin-17 (IL-17) and IL-17-related inflammatory factors and can protect neurons and promote the recovery of spinal cord injury.